Watts happening to work? The labour market effects of South Africa's electricity crisis - Haroon Bhorat; Timothy Köhler (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
Frequent electricity outages threaten to impede the benefits of expanded access achieved by many developing countries in recent decades. A large literature documents these negative effects, however almost none consider labour market effects. This paper merges labour force survey microdata with high-frequency electricity supply and demand data to provide the first estimates of the relationships between outages and labour market outcomes in South Africa, a country characterized by frequent, severe outages referred to as load shedding. Exploiting temporal variation in outage incidence and intensity, we find that load shedding is associated with significantly lower employment rates, working hours, and earnings on average. Employment appears more sensitive relative to intensive margin outcomes, threatening job creation and preservation efforts. These negative relationships, however, are not evident for low levels of load shedding, but their strength markedly increases with load shedding intensity. We document further heterogeneity by firm size and industry, highlighting the vulnerability of jobs in manufacturing. Overall, our findings suggest that the South African labour market is largely insensitive to relatively low levels of load shedding; however, high levels appear especially costly.
Keywords: J21; J23; J31; L94; 330; electricity outages; labour market; developing country; South Africa; load shedding